(untitled) (Italian Journal of Public Health, 2006)
Background: Chronic Obstructive Pulmonary Disease (COPD) represents one of the main causes of hospitalization, disability and mortality worldwide; it is predicted that by the year 2020 it will become the third leading cause of death and the fifth leading cause of disability in industrialized countries. An educational programme has been proposed to allow the COPD patient to prevent or to deal with a re- acutisation. Methods: The project involved 50 patients with a diagnosis of moderate or severe COPD. The education program included information relating to disease process, proper use of medication, energy conservation methods, and the filling in of the Saint George’s Respiratory Questionnaire (SGRQ), the Zung Self-Rating Depression Scale (ZSDS) and the State Trait Anxiety Inventory (STAI). Sociodemographic factors, assessment of living arrangements, social and family conditions were also collected. One year later the same questionnaires and learning assessment tests were re-administered. Results: The mean age of the participants was 69.7±10.4 years with a mean low income and a limited degree of education. Following the educational program, an improvement of quality of life emerged consequent to the awareness of all of the forms of support provided for the pathology and socio-economic conditions. The ability to manage their therapy and their activities of daily living have improved. The mean total score on SGRQ was 78.07±7.2 pre-program and 73.12±7.2 post-program; 52% of the patients are now within normal parameters compared to the initial 30% suffering from depression syndrome, furthermore the mean anxiety value decreased from 59.54 ± 8.6 to 54.54±7.8. The number of hospital admissions and the number of smokers were also halved. Conclusion: The improvements obtained after conducting all of the educational sessions are significant. The high value of the mean total score on SGRQ suggests overall poor health among patients affected by moderate/ severe COPD and according to other studies this population is inclined to anxiety and depression. The role of the social worker was very important because the explanation of the appropriate laws has lead to the recognition of their disability status and therefore access to established benefits. The decrease in hospitalization has brought about an economic benefit for the educational program but further studies should be carried out on more patients over longer periods of time